Haemoglobin mass measurements in professional cyclists during a long stage race: The Giro d'Italia - Artuso, P.; Bosio, A.; Guardascione, C.; Pecci, C.; Riggio, M.; Rampinini, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The total amount of haemoglobin in the blood (Hbmass) is an important determinant for VO2max (Heinicke et al., 2001). Schmdit and Prommer (2005) proposed an optimised CO re-breathing method for Hbmass determination. In two studies it was demonstrated that Hbmass is stable during short stage races (4 and 6 days long) in Under 23 male and top level female cyclists (Schumacher et al., 2008; Garvican et al., 2010). No study investigated Hbmass changes during a long stage race in top level professional cyclists. The aim of the present study was verify the influence of three weeks of race on Hbmass values of professional athletes. Methods: Nine professional cyclists (age 31±5.5 yrs, heights 178.7±5.1 cm and body mass 67.7±5.9 kg) of the same team were involved in the study. Using a simplify CO re-breathing method (Schmdit and Prommer, 2005), Hbmass of each individual was determined before (PRE, 2 days before the start), during (MID, at day 14) and after (POST, 1 day after the race) the Giro d`Italia 2011. Three athletes did not finish the race. Data of the 6 cyclists who completed the race was used for statistical analysis. The differences in Hbmass were determined using a one way ANOVA repeated measure. Results: Hbmass of the six athletes remained stable (p=0.308) during the three-week stage race (PRE, 1080±86 g; MID, 1098±66 g; POST 1100±80 g). Discussion: The main finding is that the strain induced by a long stage race like the Giro d`Italia, does not seem able to determine a decrease in Hbmass of the athletes. The results of the present study confirm other information collected during shorter stage races in different population of cyclists (Schumacher et al., 2008; Garvican et al., 2010). Since the Hbmass seems to be very stable even during the stage races, the CO rebreathing may be a useful tool to detect the use of blood doping made during the competition. The results seems to confirm also that hematocrit and haemoglobin blood concentration decreases previously reported during a long stage race are probably due to plasma volume expansion in the blood (Morkeberg et al., 2009).